PERANCANGAN TURBIN AKSIAL SATU TINGKAT UNTUK MESIN TURBOJET BERBASIS TURBOCHARGER T70 - Zulham Hidayat (Langit Biru: Jurnal Ilmiah Aviasi, 2017)
Turbocharger T70 has a type of radial turbine that has a value of 60% efficiency will be modified into a turbojet engine. To obtain a higher efficiency rating on the turbojet engine, the thesis is designed a one-stage axial turbine. This one-tiered axial turbine is expected to have an 87% efficiency and can supply power to a compressor of 120000 Watt and is also expected to be easy to manufacture . This one-tier axial turbine design method, drawn from various literatures. The design point taken in this design is the air mass (ṁ) 0.505kg / s, with the spin axis 1763.33rps. The total pressure on the turbine inlet is 3936 bar and the total temperature at the turbine inlet is 1260.417 K. The calculation result of the analysis shows the number of nozzle bar 49 and the number of rotor blades 35. The performance prediction on this one-tiered axle turbine uses Aeinley-Matieson method which yields efficiency value 87.3%. Turbine turbine blades and rotor turbine blades using Cascade software. The thickness distribution of the profile uses airfoil NACA 0012. The camber line on this 2 dimensional airfoil uses a circular arc type. Pada bilah turbin nosel dan bilah turbin rotor yang telah di bentuk selanjutnya dilakukakan analisis dengan menggunakan computational fluid dynamic (CFD). Dengan menggunakan CFD, efisiensi yang dihasilkan adalah 88.4 %, lebih besar dari prediksi performa turbin dengan menggunakan metode Aeiley-Matieson. Daya yang dihasilkan oleh turbin adalah 132436.74 Watt, sedangkan daya yang di butuhkan oleh kompresor adalah 119960.68 Watt.